KARAKTERISASI KROMOSOM UDANG GALAH (Macrobrachium rosenbergii) POPULASI SIRATU DAN MAHAKAM - Diah Asta Putri; Nurul Suwartiningsih (Scripta Biologica, 2019)
Giant freshwater prawn is one of Indonesia's freshwater prawn that has advantages such as fast growth and good meat quality. The continuous crossing of giant freshwater prawn that are closely related causes a decrease in its genetic diversity. In addition, the domestication process can also influences changes in the number and shape of chromosomes. This study is to determine the chromosome characters of domestication giant freshwater prawn (Siratu)  and those derived from natural catches (Mahakam) which are cultured in the Unit Kerja Budidaya Air Payau Balai Budidaya Udang Galah (UKBAP BBUG) Samas. Research on the characterization of chromosome of giant freshwater prawn from both natural and domesticated populations needs to be done to obtain genetic information, especially chromosome characters. This information is useful to further support the process of breeding and for the certification process of giant freshwater prawn. Chromosome length measurements were carried out using the Image Raster 3 program. The shape of the chromosomes was determined by following the classification of Levan et al. (1994) based on the Sentromer Index Value obtained. The results showed that the number of chromosomes in the population of Siratu and Mahakam were 2n = 118. The giant freshwater prawn of Siratu population had the karyotype formula 2n = 118 = 94 m + 24 sm, while the giant freshwater prawn Mahakam population had the karyotype formula 2n = 118 = 118 m.